Dampak Penggunaan Bahasa Indonesia untuk Menumbuhkan Kecintaan terhadap Negara pada Siswa Negeri 1 Cinangka - Rina Andriani; Umalihayati Umalihayati; Ana Utami Fatoni; Desma Yuliadi Saputra; Kurniati Rahmadani; Wahyu Rizki; Asmilah Asmilah; Ikhwannul Khalis; Siti Sutihat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This community service activity aimed to socialize the correct (standard) use of the Indonesian language, thereby fostering a sense of love for the country among students at SMA Negeri 1 Cinangka, Serang Regency, Banten. The goal of this activity was to instill early awareness among students to use the Indonesian language according to standardized spelling with deep love for the nation, without feeling ashamed, outdated, or merely using it as a form of identity as Indonesian citizens. It sought to rekindle a sense of nationalism in the students of SMAN 1 Cinangka by encouraging them to love and use the Indonesian language in accordance with linguistic norms.The method used in the socialization activity involved preparation, implementation, evaluation, and reporting. The socialization event was held at SMA Negeri 1 Cinangka, Cinangka Village, Serang Regency, on Monday, August 26, 2024. The participants of this activity included 207 students from SMA Negeri 1 Cinangka and the KKM (Kuliah Kerja Mahasiswa) group 38 of Cinangka. The speakers were lecturers from Bina Bangsa University with a background in the field of linguistics. The results of this activity produced an understanding and awareness among students to use the Indonesian language according to standardized spelling with deep love for the nation, without feeling ashamed, outdated, or merely using it as a form of identity as Indonesian citizens. This socialization activity is expected to rekindle a sense of nationalism in the students of SMAN 1 Cinangka, encouraging them to love and use the Indonesian language in accordance with linguistic norms.